Empowering Future Biology Teachers: Integrating STEM and Design Thinking for Effective Sustainability Learning - Pamungkas, Rahmania; Suwono, Hadi; Ibrohim; Subiantoro, Agung Wijaya (SEAQIS Journal of Science Education, 2025)
This study examines the implementation of a design project in a preservice biology teacher education course titled "Biology Education for Sustainability," aiming to enhance creativity while addressing the United Nations Sustainable Development Goals (SDGs). This work presents a comprehensive framework divided into 10 chapters, spanning approximately 16 weeks (or about three and a half months) of meetings, each corresponding to key lessons designed to empower preservice biology teachers. In addition, the project engages preservice teachers in collaborative teams to identify local environmental challenges related to specific SDGs, such as clean water, climate action, and life on land. Utilizing a design thinking framework, participants engage in brainstorming, prototype development, and iterative feedback that lead to the fostering of innovative solutions. Moreover, data were collected through pre- and post-project surveys, reflective journals, and presentations to assess the impact on creativity, understanding of the SDGs, and confidence in teaching sustainability concepts. The results indicate significant improvements in creative problem-solving skills and a deeper awareness of the SDGs, along with increased motivation to integrate sustainability into their future teaching practices. As a result, this experiment highlights the effectiveness of experiential learning in the "Biology Education for Sustainability" course, preparing preservice teachers to address global challenges through innovative and creative educational strategies.